2016
DOI: 10.1055/s-0036-1594017
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia and the Risk of Bronchopulmonary Dysplasia in Preterm Infants Less Than 32 Weeks' Gestation

Abstract: Angiogenesis is essential for normal lung development. The objective of our study was to test the hypothesis that preeclampsia, an antiangiogenic state, is a risk factor for bronchopulmonary dysplasia (BPD). Prospective cohort study of infants less than 32 weeks' gestation born to mothers with preeclampsia between January 2007 and June 2010 at a single tertiary care center. Their BPD outcome was compared with infants born to the next two normotensive mothers with a ± 1 week gestational age difference. BPD was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 57 publications
1
17
0
1
Order By: Relevance
“…Lastly, Soliman et al . didn’t find any association between preeclampsia and BPD development in a Canadian population of premature less than 32 week’s gestation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, Soliman et al . didn’t find any association between preeclampsia and BPD development in a Canadian population of premature less than 32 week’s gestation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 Babies born at the threshold of viability, small for gestational age, or to mothers with chorioamnionitis are prone to develop various complications such as respiratory distress syndrome, hypoglycemia, patent ductus arteriosus, and BPD. [19][20][21][22] Their clinical features, such as increased ventilatory settings, poor perfusion, or simply being "less active," may not be easily distinguished from infectious etiologies in the very beginning. Given the immature immune system development in preterm infants, a low threshold for sepsis evaluation with empirical antimicrobial coverage is not uncommon to avoid potentially deleterious outcomes of fulminant sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen studies reported data on BPD28 (15,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) and metaanalysis could not find a significant association between maternal smoking and this outcome (RR 1.021, 95% CI 0.924-1.129, p = 0.681) (Figure 2). In contrast, the meta-analysis of the 17 studies that reported data on BPD36 (7,8,16,39,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) showed a significant association of maternal smoking with this outcome (RR 1.126, 95% CI 1.008-1.259, p = 0.036) (Figure 3). According to the GRADE methodology, the quality of the evidence on the association between maternal smoking and BPD36 was rated as low because of moderate RoB (see above) and low magnitude of the association (20).…”
Section: Meta-analysismentioning
confidence: 94%